FDA Facilitated Regulatory Pathways: Visualizing Their Characteristics, Development, and Authorization Timelines - Liberti, Lawrence; Bujar, Magda; Breckenridge, Alasdair; Hoekman, Jarno; McAuslane, Neil; Stolk, Pieter; Leufkens, Hubert (Frontiers in Pharmacology, 2017)
The FDA has 4 facilitated regulatory pathways (FRPs): Fast Track (FT), Breakthrough Therapy (BTD), Priority Review (PR) and Accelerated Approval (AA). Only PR specifies an expedited review timeline (6 months). Therefore, we sought to determine to what extent the combination of two or more FRPs influenced development and approval times. We developed a “metro map” to illustrate FRP elements and their influence on review times. We assessed 125 new active substances (approved January 2013 - December 2015) 74 of which used one or more FRPs. For these 74, development times ranged from 1,458 (BTD+PR+AA) to 3,515 days (PR). PR alone had a median approval time of 242 days. The most common combination was FT+PR (median approval 292 days, n=21). The fastest approval times were for PR+FT+BTD+AA (145 days) and PR+BTD+AA (166 days). Our findings support the combination of FRPs for shortening development and review times beyond that provided by PR alone.